A generalized Blakers–Massey theorem. Issue 4 (7th September 2020) - Anel, Mathieu; Biedermann, Georg; Finster, Eric; Joyal, André
Abstract: We prove a generalization of the classical connectivity theorem of Blakers–Massey, valid in an arbitrary higher topos and with respect to an arbitrary modality, that is, a factorization system ( L, R ) in which the left class is stable by base change. We explain how to rederive the classical result, as well as the recent generalization of Chachólski, Scherer and Werndli ( Ann. Inst. Fourier 66 (2016) 2641–2665). Our proof is inspired by the one given in homotopy‐type theory in Favonia et al . (2016).